Sodium Channels as Targets for Volatile Anesthetics - Herold, Karl F.; Hemmings, Hugh C. (Frontiers in Pharmacology, 2012)
The molecular mechanisms of modern inhaled anesthetics although widely used in clinical settings are still poorly understood. Considerable evidence supports effects on membrane proteins such as ligand- and voltage-gated ion channels of excitable cells. Na+ channels are crucial to action potential initiation and propagation, and represent potential targets for volatile anesthetics. Inhibition of presynaptic Na+ channels leads to reduced neurotransmitter release at the synapse and could therefore contribute to the mechanisms by which volatile anesthetics produce their characteristic effects: amnesia, unconsciousness, and immobility. Early studies on crayfish and squid giant axon showed inhibition of Na+ currents by volatile anesthetics. Subsequent studies using native neuronal preparations and heterologous expression systems with various mammalian Na+ channel isoforms implicated inhibition of presynaptic Na+ channels in anesthetic actions. Volatile anesthetics reduce peak Na+ current and shift the voltage of half-maximal steady-state inactivation towards more negative potentials, thus stabilizing the fast-inactivated state. Furthermore recovery from fast-inactivation is slowed together with an enhanced use-dependent block during pulse train protocols. These effects can reduce neurotransmitter release by depressing presynaptic excitability, depolarization and Ca entry, and ultimately transmitter release. This reduction in transmitter release is more portent for glutamatergic vs. GABAergic terminals. Involvement of Na+ channel inhibition in mediating the immobility caused by volatile anesthetics has been demonstrated in animal studies, in which intrathecal infusion of the Na+ channel blocker tetrodotoxin increases volatile anesthetic potency, whereas infusion of the Na+ channels agonist veratridine reduces anesthetic potency. These studies indicate that inhibition of presynaptic Na+ channels by volatile anesthetics is involved in mediating some of their effects.